El poder de revocar los actos administrativos - Barbe Pérez, Héctor (Revista de Derecho Público, 1963)
In this article, the content of the power to revoke is outlined in its objective and subjective aspects, as well as it seeks to establish a clear differentiation between it and the power to annul, in the understanding that both are exercised from the administrative authority.